Healthy Eating: Improving Your Convenience Foods - Emily Minton (EDIS, 2012)
Convenience foods offer many benefits, but they generally have a low nutritional quality compared to other foods. You can improve the nutritional quality by adding vegetables, fruit, and/or meat and meat alternatives. This 2-page fact sheet was written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, May 2012.